Techniques of hepatic arterial reconstruction in liver transplantation - Yilmaz, S; Kutluturk, K; Usta, S; Akbulut, S (2022)
Background Hepatic artery reconstruction is an essential part of liver transplantation. This difficult stage of the operation is even more demanding in living donor liver transplantation than in deceased donor liver transplantation. One of the most important advances in hepatic artery reconstruction for living liver grafts was the introduction of microsurgical techniques involving an operative microscope or surgical loupe. Many surgical reconstruction techniques have been used in this field. Purpose In this article, first, we will talk about the hepatic artery reconstruction techniques that are frequently used in deceased donor liver transplantation, and afterward, we will talk about the hepatic artery reconstruction techniques used in living donor liver transplantation, which include the hepatic artery reconstruction technique we use and call "one stay corner suture technique". Conclusions We think high-volume transplant centers should tend to develop a standardized technique for doing hepatic artery reconstruction with their teams. We think the "one stay corner suture technique" can be easily applied in centers that perform LDLT. C1 [Yilmaz, Sezai; Kutluturk, Koray; Usta, Sertac; Akbulut, Sami] Inonu Univ, Fac Med, Dept Surg, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Yilmaz, Sezai; Kutluturk, Koray; Usta, Sertac; Akbulut, Sami] Inonu Univ, Fac Med, Liver Transplant Inst, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. C3 Inonu University; Inonu University